THE PARADIGM SHIFT OF LEARNING ORGANIZATIONS: A SYSTEMATIC LITERATURE REVIEW OF KNOWLEDGE MANAGEMENT IN THE ERA OF HUMAN-AI HYBRID INTELLIGENCE (International Journal of Cultural and Social Science, 2026)
The conceptual landscape of organizational development has undergone a radical transformation, primarily driven by the maturation of digital ecosystems and global disruptions. This systematic review examines the paradigm shift of learning organizations (LO), tracing the evolution from geographical workforce distribution to cognitive human-AI synergy. By synthesizing core literature, the study identifies critical mechanisms for tacit knowledge transfer, including digital-tacit synthesis and hybrid analytical modeling. The findings reveal that Organizational Learning Culture (OLC) remains the indispensable anchor for sustainable performance, while human-machine trust serves as the pivotal psychological gatekeeper for knowledge management success. This research proposes a Socio-Technical Hybrid Learning Ecosystem (STH-LE) framework, which bridges the gap between seminal organizational theories and the contemporary intelligence-driven reality. The study concludes with a future research agenda focusing on the ethical dimensions of AI-generated knowledge and the long-term sustainability of hybrid learning cultures.